Tensile membrane action in reinforced concrete slab - Wahyudi, Trieska Yokhebed (2010)
Unforeseen events, such as fire, impact, or blast have a potency to damage a key structural element of a building which, in turn, may lead to a partial or total collapse of the structures. The disproportionate total damage with respect to the original cause is commonly termed progressive collapse. One of the key structural elements which have high potential for progressive collapse when damaged is a penultimate column.